How should the value of statistical life be measured? The effect of the disparity between the measures of willingness to pay and willingness to accept - Mahasuweerachai, Phumsith (EEPSEA, 2017)
This is repost introduce about how should the value of statistical life be measured? The effect of the disparity between the measures of willingness to pay and willingness to accept.